A New Phenolic Amide from Stems of Cassia fistula and Their Anti-Tobacco Mosaic Virus Activities - Liu, Guiyou; Yang, Juanxia; Wang, Huan; Lou, Jie; Li, Limei; Gao, Xuemei; Hu, Qiufen; Ye, Yanqing (Asian Journal of Chemistry, 2014)
A new phenolic amide, (E)-3-(3,4-dihydroxyphenyl)-N-[2-(4-methoxyphenyl)-2-oxoethyl]-prop-2-enamide (1) was isolated from the stems of Cassia fistula. Its structure was elucidated by spectroscopic methods, including extensive 1D- and 2D-NMR techniques. Compound 1 was also evaluated for its anti-tobacco mosaic virus (anti-TMV) activity and it exhibit potential anti-TMV activity with inhibition rates of 16.2 %.